Mapping of the Cladosporium fulvum resistance gene Cf-16, a major gene involved in leaf mold disease in tomato - Zhang, Dongye; Li, Huijia; Liu, Guan; Xie, Libo; Feng, Guojun; Xu, Xiangyang (Frontiers in Genetics, 2023)
Tomato (Solanum lycopersicum) is widely cultivated and consumed worldwide. Tomato leaf mold, caused by Cladosporium fulvum, is one of the most devastating diseases in tomato production. At present, some tomato leaf mold resistance (Cf series) genes used in production gradually lose resistance due to the continuous and rapid differentiation of C. fulvum physiological races. The Cf-16 gene derived from the 'Ontario7816' tomato cultivar has shown effective resistance in field trials for many years, but few studies have reported on the mapping of the Cf-16 gene, which has not been cloned, limiting its utilization in tomato breeding. Here, we mapped Cf-16 using a novel comprehensive strategy including bulk segregation analysis (BSA), genome resequencing and SSR molecular markers. A genetic analysis revealed that Cf-16 resistance in 'Ontario7816' is controlled by one major dominant locus. The Cf-16 gene was mapped in a region of 2.6 cM at chromosome 6 between two markers, namely, TGS447 and TES312, by using an F2 population from a cross between the resistant cultivar 'Ontario7816' and susceptible line 'Moneymaker.' Two nucleotide-binding-site-leucine-rich repeat (NBS-LRR) resistance genes, namely, XM_004240667.3 and XM_010323727.1, were identified in this interval. They are strong candidates for the Cf-16 gene. The mapping of Cf-16 may speed up its utilization for breeding resistant tomato varieties and represents an important step forward in our understanding of the mechanism underlying resistance to tomato leaf mold.